Intramuscular Low-grade Fibromyxoid Sarcoma: A Case Report - Kuo-Sheng Liao; Wan-Ting Huang; Sheau-Fang Yang; Song-Hsiung Chien; Tsyh-Jyi Hsieh; Chee-Yin Chai; Chun-Chieh Wu (Kaohsiung Journal of Medical Sciences, 2009)
Low-grade fibromyxoid sarcoma (LGFMS) is a rare neoplasm that commonly arises in the deep soft tissues of the lower extremities, particularly in the thigh. LGFMS occurs preferentially in young male adults. The microscopic appearance of LGFMS exhibits bland fibroblastic spindle cells with a whorled or linear arrangement in fibrous and myxoid areas. Although LGFMS has a deceptively benign histologic appearance, local recurrence and late metastases have frequently been reported. Diagnosis of LGFMS is still difficult because of its characteristic bland-looking histologic features that can be confused with other benign or low-grade fibromyxoid lesions. Although immunohistochemical staining can offer an overview of the differential diagnosis of myxoid tumors of soft tissue, it is sometimes limited for diagnosis of LGFMS. However, recent cytogenetic and molecular analyses have provided significant improvements in the diagnosis of LGFMS. Such analyses have demonstrated that most cases of LGFMS have a characteristic t (7,16) (q33;p11) translocation, resulting in the FUS-CREB3L2 fusion gene. We report a 29-year-old female who presented with a LGFMS located in the soleus muscle of her left lower leg. Preoperative imaging suggested the possibility of an intramuscular histiocytoma of the left soleus muscle. In conclusion, diagnosis of LGFMS can be challenging in routine practice in surgical pathology because of its bland-looking features. The immunohistochemical and ultrastructural findings were consistent with the fibroblastic properties of LGFMS. Cytogenetic and/or molecular genetic analyses can be used as ancillary diagnostic tools for LGFMS.